Genetic regulation of defence responses in cotton to insect herbivores. Issue 5 (13th September 2017) - Chu, Bo; Zhang, Shuai; Wang, Li; Zhu, Xiang-Zhen; Luo, Jun-Yu; Wang, Chun-Yi; Lü, Li-Min; Cui, Jin-Jie
Abstract : Ghppo1 expression was upregulated by infestations of first instar H. armigera larvae and applications of Me-JA. In contrast, neither third instar larvae nor Me-SA increased Ghppo1 expression levels in cotton plants. Additionally, cotton polyphenol oxidase activities were upregulated by first instar H. armigera larvae and Me-JA, but not by third instar larvae or Me-SA. Expressing the Gossypium hirsutum polyphenol oxidase gene Ghppo1 in transgenic Arabidopsis thaliana plants negatively affected H. armigera development. The expression of key JA signaling pathway genes was induced by infestation of first instar H. armigera larvae. Moreover, plants previously treated with first instar H. armigera larvae exhibited significantly increased resistance to third instar H. armigera. Abstract: Induced defences play a key role in plant resistance against herbivores, and mediate interactions between phytophagous arthropods and plants via genes and signal pathways. Here, we examined the interaction between Helicoverpa armigera and cotton and the subsequent regulation of cotton defences. Quantitative real-time PCR data indicated that Ghppo1 expression was up-regulated by infestations of first instar H. armigera larvae and applications of methyl jasmonate (Me-JA). In contrast, neither third instar larvae nor methyl salicylate (Me-SA) increased Ghppo1 expression levels in cotton plants. Additionally, cotton polyphenol oxidase activities were up-regulated by first instar H. armigera larvae and Me-JA, but not by third instar larvae or Me-SA. Expressing the Gossypium hirsutum polyphenol oxidase gene Ghppo1 in transgenic Arabidopsis thaliana plants negatively affected H. armigera development. The expression of key jasmonic acid signaling pathway genes (i.e. GhAOS and GhCOI1 ) was induced by infestation of first instar H. armigera larvae. Moreover, plants previously treated with first instar H. armigera larvae exhibited significantly increased resistance to third instar H. armigera . Our findings confirm that H. armigera affects cotton defence gene expression levels to induce herbivore resistance. Additionally, Ghppo1 expression is mediated by jasmonic acid, but not salicylic acid, and may be involved in the interaction between insect herbivores and cotton defence responses.